2021
DOI: 10.1139/cjpp-2020-0721
|View full text |Cite
|
Sign up to set email alerts
|

Fluoxetine-induced hepatic lipid accumulation is linked to elevated serotonin production

Abstract: Fluoxetine, a commonly prescribed selective serotonin reuptake inhibitor antidepressant, has been shown to increase hepatic lipid accumulation, a key factor in the development of non-alcoholic fatty liver disease. Interestingly, fluoxetine has also been reported to increase peripheral serotonin synthesis. As emerging evidence suggests that serotonin may be involved in the development of non-alcoholic fatty liver disease we sought to determine if fluoxetine-induced hepatic lipid accumulation is mediated via alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Long‐term SSRI use is associated with increased weight gain, dyslipidemia, and new‐onset type 2 diabetes (Ferguson, 2001; Jerrell, 2010; Raeder et al, 2006; Sussman & Ginsberg, 1998; Yoon et al, 2013). Moreover, animal and cell culture experiments have shown that fluoxetine exposure increases hepatic triglyceride content and lipid accumulation, hallmarks of NAFLD (Ayyash & Holloway, 2021; De Long et al, 2015; Feng et al, 2012; Lu et al, 2020; Pan et al, 2018; Xiong et al, 2014). While the mechanisms by which fluoxetine leads to hepatic steatosis are not fully elucidated, there is evidence that altered prostaglandin production may be a key mediator of fluoxetine‐induced lipid accumulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Long‐term SSRI use is associated with increased weight gain, dyslipidemia, and new‐onset type 2 diabetes (Ferguson, 2001; Jerrell, 2010; Raeder et al, 2006; Sussman & Ginsberg, 1998; Yoon et al, 2013). Moreover, animal and cell culture experiments have shown that fluoxetine exposure increases hepatic triglyceride content and lipid accumulation, hallmarks of NAFLD (Ayyash & Holloway, 2021; De Long et al, 2015; Feng et al, 2012; Lu et al, 2020; Pan et al, 2018; Xiong et al, 2014). While the mechanisms by which fluoxetine leads to hepatic steatosis are not fully elucidated, there is evidence that altered prostaglandin production may be a key mediator of fluoxetine‐induced lipid accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term SSRI use is associated with increased weight gain, dyslipidemia, and new-onset type 2 diabetes (Ferguson, 2001;Jerrell, 2010;Raeder et al, 2006;Sussman & Ginsberg, 1998;Yoon et al, 2013). Moreover, animal and cell culture experiments have shown that fluoxetine exposure increases hepatic triglyceride content and lipid accumulation, hallmarks of NAFLD (Ayyash & Holloway, 2021;Feng et al, 2012;Lu et al, 2020;Pan et al, 2018;Xiong et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluoxetine induced hepatic lipid accumulation through upregulation of TPH1 expression and subsequent increased blood concentration of 5-HT. 57 …”
Section: The Roles Of Tryptophan and Its Metabolites In Inflammationmentioning
confidence: 99%
“…Patients who received TCAs (imipramine, tianeptine) [62,63] and SNRIs (venlafaxine, duloxetine) developed hepatic steatosis [64,65]. A clinical study showed that fluoxetine, an SSRI, increased serum triglyceride levels and hepatic lipid accumulation [66,67]. A clinical trial on the cardiometabolic benefits of lorcaserin, a 5-HT2C receptor agonist, showed that lorcaserin significantly improved fatty liver in obese adults, and the effect remained significant even after controlling for fat mass and change in body weight [68].…”
Section: Human Molecular Biology and Clinical Evidence Of The Association Between 5-ht And Nafldmentioning
confidence: 99%